PEMBERDAYAAN KELOMPOK TANI WANITA NAGARI III KOTO AUR MALINTANG TIMUR DALAM PROGRAM TANAMAN KANGKUNG HIDROPONIK - Susila Bahri; Selfigo Chaniago; Tri Mayliza (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
The people of Nagari III Koto Aur Malintang Timur used their vast land to grow rice, corn and peanuts. Because of lack of agriculture land and knowledge about hydroponics cultivation, they brought in the goods from other areas for satisfying their other basic needs such as vegetables. Hydroponics training was given to Women Farmer Group (KTW) in the nagari so that those people especially KTW could meet their own demands for kale vegetables. Training with a direct practice method in the field implemented in 24 days in which it passed through the stages of seedling, transplanting, growing and harvesting. According to the results of field practice based on the training, the people can understand how the hydroponics system works especially for ground kale plant. Finally, they could directly grow and harvest them in their own yards. In fact, kale plants produced from hydroponics look cleaner when compared to kale plants without hydroponics.